PENGARUH KUALITAS PELAYANAN DAN ETOS KERJA ISLAMI TERHADAP KEPUASAN MUZAKKI PADA BAZNAS KABUPATEN TUBAN - Setyawati, Tri; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2024)
Zakat has an important role in helping overcome the problem of poverty that occurs in Indonesia. This research aims to identify the influence of service quality and Islamic work ethic on muzakki satisfaction at Baznas Tuban Regency. This research uses a quantitative method with an associative approach and uses a probability sampling technique, namely simple random sampling. Data was collected using a questionnaire and measured using a Likert scale. Multiple Linear Regression data analysis technique using the SPSS program. The research results show that partially service quality has a positive and significant effect on muzakki satisfaction, Islamic work ethic has a positive and significant effect on muzakki satisfaction. Meanwhile, simultaneously the quality of service and the Islamic work ethic influence muzakki satisfaction at Baznas Tuban Regency. It is hoped that the results of this research can become a reference in zakat management in Indonesia.